비대칭적 중방향 교통류 대응을 위한 이동식 중앙분리대 활용 버스전용차로 도입 전략 분석 - 김태완; 정연식; 전교석; 김원길; Kim, Taewan; Chung, Younshik; Jeon, Gyo Seok; Kim, Wongil (KSCE Journal of Civil and Environmental Engineering Research, 2022)
Lane management with a central variable lane(s) (or reversible lane) where the traffic flow is temporarily reversed in one or more lanes during peak periods has been evaluated as an effective strategy to alleviate congestion caused by tidal traffic flows. However, due to traffic safety issues, such a movable barrier system can be considered as an alternative to supplement the existing its operation facilities such as static and/or dynamic signs and special pavement markings. In addition, when combined with a bus exclusive lane strategy, its effectiveness could be greatly increased. The objective of this study is to propose a feasibility analysis procedure for operational strategies of a bus-exclusive lanes using a barrier transfer system (BTS) for urban expressways. To this end, a case study was conducted on two urban expressways on the west side of the Han River in Seoul. As a result, temporary operation during rush hour in the morning was found to be most effective. The results presented in this study are expected to serve as a basis for establishing bus-exclusive lane operation strategies using similar systems in the future. 중앙 가변차로제는 비대칭적 중방향 교통류에 의한 혼잡을 완화하기 위한 효과적인 대안으로 평가되어 왔으나, 교통안전에 대한 문제로 국내에서는 점차 사라지고 있다. 이동식 중앙분리대 시스템은 교통안전 문제를 보완하기 위한 대안으로 활용될 수 있으며, 일시적 버스전용차로 운영과 결합하여 효율적으로 교통혼잡을 관리할 수 있을 것으로 평가된다. 본 연구는 도시고속도로 대상으로 이동식 중앙분리대 활용 버스전용차로 운영 전략에 대한 설정 절차 및 최적의 대안에 대한 평가 절차를 제안하고자 하였다. 이를 위해 서울시 한강변 서측 2개의 도시고속도로 대상 사례연구를 진행하였으며, 그 결과 오전 혼잡시간대 일시적 운영이 가장 효과적인 것으로 나타났다. 본 연구에서 제시된 결과는 향후 유사 시스템을 활용한 버스전용차로 운영 전략 수립의 기반이 될 것으로 기대된다.